FORMATION OF MARKETING STRATEGY OF HIGHER EDUCATION INSTITUTIONS - KOVALCHUK, SVITLANA; MARTYNOVA, LILIYA; TANASIICHUK, ALONA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The study found that the strategic trend of higher education is to find and implement an effective marketing strategy to ensure the competitiveness of the university in the target market of educational services, which involves the development and promotion of modern and innovative educational products of high quality. It is proved that the primary task that ensures the effective operation of the university in the market of educational services is the formation and implementation of its cost-effective marketing strategy. The classic marketing strategies that can be used by a higher education institution are identified and the focus is on the fact that the marketing strategy of a higher education institution is an integration tool and is related to optimizing the mission of the educational institution by choosing the best directions. increase the competitiveness of the university in the market of educational services. The results of the study substantiate that the marketing strategy of a higher education institution should be considered as a plan of systemic measures of long-term and comprehensive nature, special features of which are research and analysis of factors shaping the market of educational services, systematic analysis and planning of marketing activities aimed at sustainable growth. effectiveness and efficiency of higher education institutions. It is important to pay special attention to the choice and justification of a specific strategy to cover a specific educational market and the search for real competitive advantages of higher education in this area. The directions of increase of adaptability of marketing strategy of ZVO are offered, which provide formation of adaptive marketing efforts, characterized by systematic search and realization of primary and secondary educational needs, introduction of creative innovations and their commercialization. When developing and implementing the marketing strategy of the Free Economic Zone, it is proposed to study the dynamics of its development indicators, which will allow the company to meet consumer demands and as a result obtain the desired financial results. For this purpose, a balanced system of indicators of higher education development is proposed, which includes groups of indicators that influence the formation of desired financial results, the formation of relationships with customers, consumers of educational services, the formation of internal processes of higher education, the quality of educational services. programs according to the requirements of the time. It is substantiated that a balanced system of indicators is aimed at increasing the effectiveness of marketing management of the university strategy and at the same time improving it under the influence of changing consumer needs, development of scientific and technical achievements, which will allow higher education to train highly qualified specialists, make scientifically sound, innovative, technological decisions. will have practical significance. In the proposed balanced system of indicators of development of ZVO the marketing block is detailed in the context of structure of the marketing purposes of activity of high school and the indicators corresponding to them.